Practical methods for biocatalysis and biotransformations 2 - Whittall, John; Sutton, Peter (Peter W.) (Wiley, 2012)
Biocatalysts are increasingly used by chemists engaged in fine chemical synthesis within both industry and academia. Today, there exists a huge choice of high-tech enzymes and whole cell biocatalysts, which add enormously to the repertoire of synthetic possibilities. Practical Methods for Biocatalysis and Biotransformations 2 is a "how-to" guide that focuses on the practical applications of enzymes and strains of microorganisms that are readily obtained or derived from culture collections. The sources of starting materials and reagents, hints, tips and safety advice (where appropri.